Psychophysiological characteristics of teenage athletes in cyclic sports - Vedernikova E.V.; Bugaychuk T.V.; Galiev R.R.; Kolodkin A.S. (Theory and Practice of Physical Culture, 2024)
Objective of the study is to identify the psychophysiological status of teenage athletes involved in cyclic sports. Methods and structure of the study. The work assessed the psychophysiological characteristics of 85 teenage athletes in cyclic sports: biathlon, speed skating and swimming using the psychophysiological testing device UPFT-1/30 – «Psychophysiologist». The level of reactive and personal anxiety was also determined. Results and conclusions. The results of the study made it possible to obtain a psychophysiological portrait of teenage athletes involved in cyclic sports. We showed that biathletes had better work efficiency, strength and endurance of nervous processes. In swimmers, inhibition processes prevailed over excitation processes and were characterized by greater mobility. The number of accurate reactions among the athletes we studied turned out to be below the age norm, which is associated with the low dynamics of the competitive situation in these sports. Thus, the data obtained can be used in the training process and in preparing teenage athletes of cyclic sports for competitions.